Antibiotic prophylaxis and hospitalization of horses subjected to median laparotomy: gut microbiota trajectories and abundance increase of Escherichia - Kauter, Anne; Brombach, Julian; Lübke-Becker, Antina; Kannapin, Dania; Bang, Corinna; Franzenburg, Sören; Stoeckle, Sabita D.; Mellmann, Alexander; Scherff, Natalie; Köck, Robin; Guenther, Sebastian; Wieler, Lothar H.; et al. (Frontiers in Microbiology, 2023)
Introduction Horse clinics are hotspots for the accumulation and spread of clinically relevant and zoonotic multidrug-resistant bacteria, including extended-spectrum β-lactamase producing (ESBL) Enterobacterales. Although median laparotomy in cases of acute equine colic is a frequently performed surgical intervention, knowledge about the effects of peri-operative antibiotic prophylaxis (PAP) based on a combination of penicillin and gentamicin on the gut microbiota is limited. Methods We collected fecal samples of horses from a non-hospitalized control group (CG) and from horses receiving either a pre-surgical single-shot (SSG) or a peri-operative 5-day (5DG) course of PAP. To assess differences between the two PAP regimens and the CG, all samples obtained at hospital admission (t0), on days three (t1) and 10 (t2) after surgery, were screened for ESBL-producing Enterobacterales and subjected to 16S rRNA V1–V2 gene sequencing. Results We included 48 samples in the SSG (n = 16 horses), 45 in the 5DG (n = 15), and 20 in the CG (for t0 and t1, n = 10). Two samples of equine patients receiving antibiotic prophylaxis (6.5%) were positive for ESBL-producing Enterobacterales at t0, while this rate increased to 67% at t1 and decreased only slightly at t2 (61%). Shannon diversity index (SDI) was used to evaluate alpha-diversity changes, revealing there was no significant difference between horses suffering from acute colic (5DG, SDImean of 5.90, SSG, SDImean of 6.17) when compared to the CG (SDImean of 6.53) at t0. Alpha-diversity decreased significantly in both PAP groups at t1, while at t2 the onset of microbiome recovery was noticed. Although we did not identify a significant SDImean difference with respect to PAP duration, the community structure (beta-diversity) was considerably restricted in samples of the 5DG at t1, most likely due to the ongoing administration of antibiotics. An increased abundance of Enterobacteriaceae, especially Escherichia, was noted for both study groups at t1. Conclusion Colic surgery and PAP drive the equine gut microbiome towards dysbiosis and reduced biodiversity that is accompanied by an increase of samples positive for ESBL-producing Enterobacterales. Further studies are needed to reveal important factors promoting the increase and residency of ESBL-producing Enterobacterales among hospitalized horses.